2021
DOI: 10.1155/2021/6325578
|View full text |Cite
|
Sign up to set email alerts
|

Urban Road Network Emergency: An Integrative Vulnerability Identification Method

Abstract: The vulnerability of an urban road network is affected by many factors, such as internal road network layout, network structure strength, and external destructive events, which have great uncertainty and complexity. Thus, there is still no unified and definite vulnerability analysis scheme available to cities. This paper proposes an integrative vulnerability identification method for urban road networks, which mainly relates to the vulnerability connotation and characteristics analysis of urban road networks d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[22] Because the final goal of studying complex networks is to control and regulate them, many works have explained the inner relationship between structural characteristics and network control. [23][24][25][26][27][28][29] Furthermore, for practical problems in real control, control strategies, including energy requiring, [30][31][32][33][34] control modes, [35] and optimal control, [36][37][38] have also been considered. Reference [37] demonstrated that the control energy is involved with Gramian matrix and proposed optimal algorithm for driver nodes selection.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Because the final goal of studying complex networks is to control and regulate them, many works have explained the inner relationship between structural characteristics and network control. [23][24][25][26][27][28][29] Furthermore, for practical problems in real control, control strategies, including energy requiring, [30][31][32][33][34] control modes, [35] and optimal control, [36][37][38] have also been considered. Reference [37] demonstrated that the control energy is involved with Gramian matrix and proposed optimal algorithm for driver nodes selection.…”
Section: Introductionmentioning
confidence: 99%